A state-of-the-art review on fibre-reinforced geopolymer composites - Noor Abbas, Al-Ghazali; Abdul Aziz, Farah Nora Aznieta; Abdan, Khalina; Mohd Nasir, Noor Azline; Huseien, Ghasan Fahim (Elsevier, 2022)
Cement industries that produce the primary component of concrete remain one of the main challenges to the world since they change the climate and possess a negative impact on sustainability. Due to climate change, the earth's temperature has increased and reached a higher level in recent years that in turn results in a distressed environment for all living beings for survival. All the consequences that scientists warned would occur as a result of global climate change in the past are now occurring: rapid sea-level rise, sea ice loss and longer, more intense heat waves. Geopolymer materials are considered as one of the solutions to reduce greenhouse gas emissions from the cement industry. Geopolymers provide the industry with great potential and sustainable alternatives to ordinary Portland cement (OPC). However, when subjected to flexure and tension stresses, the geopolymer's inherent brittleness displays drawbacks like OPC; both need fibre reinforcement to control cracks propagation, enhance toughness and deformation. As a result, the development of fibre-reinforced geopolymer composites (FRGC) has attracted increased attention, with a wide range of fibres being used. This study presents a review of the published papers on the FRGC; the research papers were reviewed and classified into sub-categories depending on the fibres type. The physical, mechanical and microstructural properties of geopolymer composites were discussed in detail. By reviewing the literature, it is evident that the FRGC can be a potential solution for structural applications with excellent performance. The improvements in geopolymer properties with the fibre addition have paved the way for further studies in this regard to exploring its performance in unused areas.